Study of The Ruling of The Shipping Court in Burning Boat Accidents That Impact Losses Passenger as Consumers - Gilalo, Jerymianus; Mulyadi, Mulyadi; Ilyanawati, R Yuniar Anisa; Gilalo, Jacobus Jopie (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Passenger ship accidents frequently occur in Indonesian waters, resulting in injuries and fatalities. Unfortunately, the affected individuals only receive partial compensation from their travel insurance and are not granted full compensation under their consumer rights as outlined in Act Number 8 year of 1999 about Consumer Protection. This leaves them feeling disheartened about reclaiming their lost possessions.Purposes of the Research: The article delves into the legal rights of passengers impacted by sea transportation accidents, covering physical injury, loss of life, and property damage. The Shipping Court conducted a thorough investigation into the incident involving KM Express Cantika 77 on October 24, 2022, with a strong focus on uncovering the cause and implications.Methods of the Research: With normative juridical research methods, and based on literature data and the decision of the Shipping Court in the case of the burning of the Ferry KM Express Cantika 77 on October 24 2022 at 13.20 WITA in Naikliu Waters. By analyzing using a qualitative approach to determine the rights of passengers who got an accident.Results of the Research: The Indonesian Shipping Court decides on passenger ship accident cases only by examining the causes and impacts of the accident. It is recommended that the Shipping Court become a special court, like other special courts such as the Industrial Relations, Fisheries, and Forestry Courts. These reforms will allow the Court to examine and prosecute based on the criminal, civil, and administrative aspects of shipping incidents.